Aspiration thrombectomy prior to percutaneous coronary intervention in ST-elevation myocardial infarction: a systematic review and meta-analysis. Issue 1 (December 2016) - El Dib, Regina; Spencer, Frederick; Suzumura, Erica; Gomaa, Huda; Kwong, Joey; Guyatt, Gordon; Vandvik, Per
Abstract Background Trials of aspiration thrombectomy (AT) prior to primary percutaneous intervention (PCI) in patients with ST-segment elevation MI (STEMI) have shown apparently inconsistent results and therefore generated uncertainty and controversy. To summarize the effects of AT prior to PCI versus conventional PCI in STEMI patients. Methods Searches of MEDLINE, EMBASE and CENTRAL to June 2015 and review of reference lists of previous reviews. We included randomized controlled trials (RCTs) comparing AT prior to PCI with conventional PCI alone. Pairs of reviewers independently screened eligible articles; extracted data; and assessed risk of bias. We used the GRADE approach to rate overall certainty of the evidence. Results Among 73 potential articles identified, 20 trials including 21, 660 patients were eligible; data were complete for 20, 866 patients. Moderate-certainty evidence suggested a non statistically significant decrease in overall mortality (risk ratio (RR) 0.89, 95 % confidence interval, 0.78 to 1.01, risk difference (RD) 4/1, 000 over 6 months), no impact on recurrent MI (RR 0.94, 95 % CI, 0.79 to 1.12) or major bleeding (RR 1.02, 95 % CI, 0.78 to 1.35), and an increase in stroke (RR 1.56, 95 % CI, 1.09 to 2.24, RD 3/1, 000 over 6 months). Conclusions Moderate certainty evidence suggests aspiration thrombectomy is associated with a possible small decrease in mortality (4 less deaths/1000 over 6 months) and a small increase in stroke (3 more strokes/1000 over 6 months). Because absolute effects are very small and closely balanced, thrombectomy prior to primary PCI should not be used as a routine strategy.